MANIFESTATIONS BODY OF THE BLACK CULTURE IN THE EDUCATION PHYSICS SCHOOL. (Fiep Bulletin - online, 2011)
manifestations of the black culture that were divided in agreement with the blocks of contents of the School Physical education: games, rhythmic and expressive activities, sports, fights, gymnastics, knowledge on the body, supplied following the dimensions of the contents: conceptual, proceeding and expression that experience was if structuring. The main objective was that the students could know, to live and to appreciate body manifestations of the black culture, understanding like this the different body manifestations without discrimination and nor prejudice. The objectives so that that happened became separated in two: all to work the blocks of contents of the physical education with that theme and to work the leaving of the physical education classes for other areas. Therefore we can say that the four key points that orientated this project were: Black, Body Culture, School Physical education and interdisciplinary. They announced in that project of experience 103 students of the fourth series of the evening period of the State School Antonio of Oliveira Bueno Filho in an outlying neighborhood of the city of Araraquara-SP of the year of 2009, that demonstrated interest in developing this project since in the previous year they had one month where classes went themes to subject of the black conscience. Where could live some games of African origin. The Project to the whole was developed along five months. The students lived in a practical and theoretical way all of the contents mentioned already. Being like this, we verified that those classes not just contributed for it lives her corporal of the students, but for their general experience, having obtained knowledge on the blocks of contents of the Physical education and geography, Portuguese language, recounts, mathematics and sciences.
Keywords: body culture; School Physical education; black culture